Effects of Ovariohysterectomy and Hyperbaric Oxygen Therapy on Systemic Inflammation and Oxidation in Dogs - Gautier, Anais; Graff, Emily C.; Bacek, Lenore; Fish, Eric J.; White, Amelia; Palmer, Lee; Kuo, Kendon (Frontiers in Veterinary Science, 2020)
Introduction: Hyperbaric oxygen therapy (HBOT) involves breathing 100% oxygen in a specialized compression chamber leading to hyperoxia. This treatment modality is associated with anti-inflammatory, antioxidant and healing properties in people and laboratory animals. However, there are relatively few reports that evaluate the effects of HBOT in companion animals. The goal of this study was to investigate the physiological effects of HBOT on surgically induced systemic inflammation and oxidation in dogs. Material and Methods: Twelve healthy female beagle dogs were spayed and randomized into control and HBOT groups (n=6). Both groups received conventional post-ovariohysterectomy therapy, and the HBOT group received two hyperbaric treatments at 2.0 atmosphere of absolute pressure and 100% oxygen for 35 minutes, 6 and 18 hours after surgery. Blood samples were collected 3 hours prior to ovariohysterectomy, 6, 18 and 30 hours after surgery, prior to HBOT when applicable. Inflammatory biomarkers, including C-reactive protein, circulating cytokines, and changes in iron homeostasis were evaluated at each time point to determine the effects of surgery and HBOT on inflammation. Similarly, serum total oxidant status and total antioxidant status were measured to assess the oxidative stress. Pain and incision scores were recorded and compared between groups. Results: Following ovariohysterectomy, all dogs had significantly increased serum concentrations of C-reactive protein, KC-like, IL-6, and increased unsaturated iron-binding capacity compared to their pre-surgical values (p < 0.02), while serum iron, total iron-binding capacity and transferrin saturation were significantly decreased after surgery (p < 0.02). There was no significant difference between the control group and the HBOT group for any of the variables. There were no overt adverse effects in the HBOT group. Conclusion: This is the first prospective randomized controlled study to investigate the effects of HBOT on surgically induced systemic inflammation in dogs. While elective ovariohysterectomy resulted in mild inflammation, the described HBOT protocol portrayed no outward adverse effect and did not induce any detectable pro-inflammatory, anti-inflammatory or antioxidant effects. Additional investigation is required to identify objective markers to quantify the response to HBOT and determine its role as an adjunctive therapy in dogs with more severe, complicated or chronic diseases.